Unlocking the Synergistic Promoter Role of Phosphorus in Evolving NiFe Phosphides for Enhanced Water Oxidation - Shi, Ningning; Gao, Mingcheng; Maneesha, M.; Praveen, C. S.; Liu, Panpan; Yue, Shengnan; Xie, Wangjing; Chen, Dechao; Tang, Yu; Wang, Yuanqing; Fan, Hua; Huang, Xing (Nano-Micro Letters, 2026)
Transition metal-based electrocatalysts, especially NiFe (oxy)hydroxides, represent state-of-the-art systems for the alkaline oxygen evolution reaction (OER). While structural evolution of electrocatalysts under working conditions has garnered considerable attention, as the evolved structure often dictates catalytic activity, the mechanisms driving these transformations and catalytic performance remain poorly understood. In this work, using NiFe phosphide (NiFeP) as a model system, we systematically elucidate how phosphorus guides irreversible structural transformations and boosts OER performance. Through a combination of electron microscopy, spectroscopy, and electrochemical analysis, we demonstrate that phosphorus facilitates the transformation of NiFeP into NiFe (oxy)hydroxides while retaining residual oxyanion moieties. Importantly, we reveal that phosphorus not only accelerates the active phase formation but also suppresses Fe dissolution and directly modulates the electronic structure, a dual function that has not been well-documented in the literature. The reconstructed catalyst exhibits outstanding OER activity and remarkable stability under alkaline conditions, achieving a low overpotential of 225 mV at 10 mA cm−2 and stably maintaining a current density of 500 mA cm−2 for over 100 h, ranking among the most effective OER catalysts reported in the literature. Density functional theory calculations indicated that the resulting PO43− and Fe act synergistically to regulate the redox chemistry of Ni, preventing Ni over-oxidation and enhancing electronic conductivity. Furthermore, PO43− stabilizes key OER intermediates and lower the thermodynamic energy barrier, thereby improving catalytic performance. Highlights: 1 Phosphorus drives NiFeP’s reconstruction into active NiFe (oxy)hydroxide, suppresses Fe dissolution, and modulates Ni’s electronic structure via residual PO43−. 2 PO43− and Fe synergistically act as a redox buffer, preventing Ni over-oxidation, narrowing the bandgap, and stabilizing key oxygen evolution reaction intermediates to lower the energy barrier. 3 The restructured catalyst achieves a low overpotential of 225 mV at 10 mA cm−2 and maintains stable operation in alkaline media for over 100 h at current densities up to 500 mA cm−2.